Family Structure, Race, and Wealth Ownership: A Longitudinal Exploration of Wealth Accumulation Processes - Lisa A. Keister (Levy Economics Institute of Bard College, 2000)
Researchers have documented racial inequalities in wealth ownership and have offered a variety of explanations to account for these differences. One potentially important contributing factor that has received little attention is racial differences in family structure. This paper explores racial differences in the structure of family of origin and family in adulthood and examines the impact of these differences on wealth accumulation patterns. Using the National Longitudinal Survey of Youth, I find that large family size and family disruptions in childhood are negatively associated with wealth accumulation, portfolio behavior, and wealth mobility in adulthood. My analyses suggest that family size is a more important factor determining wealth accumulation for whites than for blacks or Hispanics and that family disruption is most strongly related to wealth outcomes for Hispanics. I find that family structure in adulthood is only modestly associated with overall wealth but strongly related to portfolio behavior and wealth mobility and that these relationships are relatively fixed across racial groups. My findings lend support to arguments about the importance of the role that resource dilution plays in determining life outcomes. They also suggest that efforts to reduce racial inequality in wealth ownership may be most effective if they seek to reduce the impact of deprivation early in life.
Keywords: 330